THE EFFECTIVENESS OF THE TOTAL PHYSICAL RESPONSE METHOD TO STUDENTS' VOCABULARY MASTERY IN ELEMENTARY SCHOOL - Ata, Nabila Ismi (English Edu: Journal of English Teaching and Learning, 2023)
Vocabulary is a part of a language or the core of a language that can be arranged into sentences. Teaching to students, of course, is not only introduced orally but also teaching in physical form and instructions. One of them is the TPR method. The Total Physical Response method is a learning method that focuses on teaching language through commands accompanied by speech, then movement through physical activity, and then imitation. This study aimed to determine the effect of the TPR method on students' vocabulary mastery. This study uses pre-experimental quantitative research methods. The subjects of this study were 25 fifth-grade students. The results showed a significant difference between the pre-test and post-test. The test results were tested by data analysis in the form of Paired Sample T-Test using the SPSS 25 application. The test results show a significance value of 0.000, meaning that the value is smaller than 0.05 so H0 is rejected and H1 is accepted. So, the TPR learning method is effective in mastering students' vocabulary.